2007
DOI: 10.1111/j.1651-2227.2007.00471.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the length of initial hospital stay in very preterm infants

Abstract: Our study showed large regional variation in LOS of very preterm infants despite similar case mix. We speculate that the variation depends on differences in treatment practices and discharge criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
(28 reference statements)
1
23
0
4
Order By: Relevance
“…In our own data, the initial length of hospital stay varied between the five university hospital districts [8]. In this study, it was encouraging to notice that regional differences were not seen in the behaviour and development at 5 years of age.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In our own data, the initial length of hospital stay varied between the five university hospital districts [8]. In this study, it was encouraging to notice that regional differences were not seen in the behaviour and development at 5 years of age.…”
Section: Discussionmentioning
confidence: 66%
“…A very premature birth in the daytime [7] has also been linked to lower mortality rates of very premature infants in California, and a trend towards lower mortality of VLBWI born during office hours has been seen in comparison to those born outside office hours in Finland [5]. In Finland, differences between the university hospital district of birth have been seen in the length of initial hospital stay of VLBWI [8] and in mortality of extremely low birthweight infants (ELBWI) [9]. Tommiska et al [9] reported differences between hospital districts in short-term morbidities of ELBWI born in 1996-1997, but these differences were not further specified and were no longer found in those ELBWI born in 1999-2000.…”
Section: Introductionmentioning
confidence: 90%
“…Recent research showed regional differences in the length of stay (LOS) in the initial hospitalization for very preterm infants in Finland, which could not be explained by birth-and infant-related factors such as gestational age, gender, and mode of delivery. 11 To our knowledge, there are no studies on how LOS and rehospitalizations are associated with later chronic morbidities in preterm infants. The objective of this study was to determine the relationship between prematurityrelated morbidity and the use of hospital resources during the first 3 years of life among very preterm infants.…”
mentioning
confidence: 97%
“…In our study unit, the length of hospital stay did not shorten. Compared to the national [24] and international (Vermont Oxford Network) comparison populations, the study unit had shorter than average length of stay already at the beginning of the study.…”
Section: Tablementioning
confidence: 97%